Creative Lives - Lokuge, Chandani,Ringrose, Chris (ibidem, 2021)
South Asian Diasporic Writing—poetry, fiction literary theory, and drama by writers from India, Pakistan, and Sri Lanka now living in the UK, Canada, Australia, New Zealand, and the USA—is one of the most vibrant areas of contemporary world literature. In this volume, twelve acclaimed writers from this tradition are interviewed by experts in the field about their political, thematic, and personal concerns as well as their working methods and the publishing scene. The book also includes an authoritative introduction to the field, and essays on each writer and interviewer. The interviewers and interviewees are: Alexandra Watkins, Michelle de Kretser, Homi Bhabha, Klaus Stierstorfer, Amit Chaudhuri, Pavan Malreddy, Rukhsana Ahmad, Maryam Mirza, Shankari Chandran, Birte Heidemann, Neel Mukherjee, Anjali Joseph, Chris Ringrose, Michelle Cahill, Rajith Savanadasa, Mariam Pirbhai, Maryam Mirza, Mridula Koshy, Sehba Sarwar, Dr Angela Savage, Sulari Gentill.
9783838275444
Keywords: Essays; Reviews; Rezensionen; South Asian Diasporic; Südasiatische Diaspora; Weltliteratur; World Literature